1977
DOI: 10.1017/s0022112077001840
|View full text |Cite
|
Sign up to set email alerts
|

The lateral migration of spherical particles sedimenting in a stagnant bounded fluid

Abstract: Singular perturbation techniques are used to calculate the migration velocity of a spherical particle sedimenting, at low Reynolds numbers, in a stagnant viscous fluid bounded by one or two infinite vertical plane walls. The method is then used to study the migration of a pair of spherical particles sedimenting either in unbounded fluid or in fluid bounded by a plane vertical wall. The migration phenomenon is studied experimentally by recording the trajectory of a spherical particle settling through a viscous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
139
1
2

Year Published

1993
1993
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(164 citation statements)
references
References 17 publications
22
139
1
2
Order By: Relevance
“…For example, in the case of L periodic = 45.511, L x = 6.044, and ⌽ = 0.05 we found that x increases from 0.95 to 1.43 when Re p changes from 0.1 to 1. This behavior is reasonable since in a region of finite Re p particle sedimenting between two infinite vertical walls is shown by Vasseur and Cox [34] to migrate away from the closer wall due to a repulsive particle-wall interaction. On the other hand, as discussed in the analysis of moderate Re p by Koch [24], the particle migrates away from the wake of another particle.…”
Section: A Particle Density Distributionmentioning
confidence: 66%
“…For example, in the case of L periodic = 45.511, L x = 6.044, and ⌽ = 0.05 we found that x increases from 0.95 to 1.43 when Re p changes from 0.1 to 1. This behavior is reasonable since in a region of finite Re p particle sedimenting between two infinite vertical walls is shown by Vasseur and Cox [34] to migrate away from the closer wall due to a repulsive particle-wall interaction. On the other hand, as discussed in the analysis of moderate Re p by Koch [24], the particle migrates away from the wake of another particle.…”
Section: A Particle Density Distributionmentioning
confidence: 66%
“…On the lower end of the Re spectrum, we have to mention the perturbation analysis of Vasseur & Cox (1977). Their theory, like all other theories of its kind, is unable to follow the actual motion of the particle.…”
Section: Comparison With Other Resultsmentioning
confidence: 99%
“…In addition, two zero Dean velocity lines exist between the For a microparticle in fluid flow, because of the parabolic velocity profile of the Poiseuille flow, its upper side has a larger relative velocity (in magnitude) than its lower side. This reduces the pressure on the upper side of the particle and, consequently, F S is generated, by which the particle is pushed away from the centerline, towards the channel walls, until this force is balanced by F W [66,67]. In other words, a particle tends to follow the path along which its sides undergo a minimum difference in relative velocity.…”
Section: Theoretical Backgroundmentioning
confidence: 99%